1997
DOI: 10.1111/1467-9892.00050
|View full text |Cite
|
Sign up to set email alerts
|

Testing for long‐range dependence in the presence of shifting means or a slowly declining trend, using a variance‐type estimator

Abstract: In this paper we examine the effects of certain types of non-stationarity on the detection of long-range dependence and on the estimation of the Hurst parameter H, when using a variance-type estimator. The resulting estimate of H can be misleading when the series has either a jump in the mean or a slow trend. In such a case, plotting the logarithm of the variance versus the logarithm of the level of aggregation gives a curve which is quite different from a straight line. A method for distinguishing between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(99 citation statements)
references
References 4 publications
2
93
1
Order By: Relevance
“…A method for detecting long-range dependence even in the presence of these types of nonstationarity was recently proposed by Teverovsky and Taqqu [1997]. It is a variance-type …”
Section: Dilferenced Variance Methodsmentioning
confidence: 99%
“…A method for detecting long-range dependence even in the presence of these types of nonstationarity was recently proposed by Teverovsky and Taqqu [1997]. It is a variance-type …”
Section: Dilferenced Variance Methodsmentioning
confidence: 99%
“…Reviews of long memory can be found in Palma (2007) or Beran et al (2013). Time domain H estimation methods include the R/S statistic (Mandelbrot and Taqqu 1979;Bhattacharya et al 1983); aggregate series variance estimators (Taqqu et al 1995;Teverovsky and Taqqu 1997;Giraitis et al 1999); least squares regression using subsampling in Higuchi (1990); variance of residuals estimators in Peng et al (1994).…”
Section: Review Of Long-range Dependence Its Estimation Wavelets Anmentioning
confidence: 99%
“…This problem is considered for example by Giraitis et al (2000a). Teverovsky/Taqqu (1997) considered the behaviour of a variance-type estimator of the memory parameter by adding a model with shifts in the mean or a slowly decaying trend of the same type as in Bhattacharya et al (1983) andK unsch (1986) to the noise process. These trends are special cases of the model of Giraitis et al (2000a) and thus of the considerations below.…”
Section: Long-range Dependence and Non-monotonic Trendsmentioning
confidence: 99%